2013
DOI: 10.1186/1477-7827-11-114
|View full text |Cite
|
Sign up to set email alerts
|

IVF outcome is optimized when embryos are replaced between 5 and 15 mm from the fundal endometrial surface: a prospective analysis on 1184 IVF cycles

Abstract: BackgroundSome data suggest that the results of human in vitro fertilization (IVF) may be affected by the site of the uterine cavity where embryos are released. It is not yet clear if there is an optimal range of embryo-fundus distance (EFD) within which embryos should be transferred to optimize IVF outcome.MethodsThe present study included 1184 patients undergoing a blind, clinical-touch ET of 1–2 fresh embryos loaded in a soft catheter with a low amount of culture medium. We measured the EFD using transvagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
3
23
0
2
Order By: Relevance
“…Improved clinical outcomes have been demonstrated with particular stimulation protocols (1,2), embryo handling and culture conditions (3), technical factors, such as the use of the transfer catheter and placement of the embryo during ET, (49) and embryo selection techniques (10,11). However, identification of clinical markers of endometrial receptivity for optimization during COH remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Improved clinical outcomes have been demonstrated with particular stimulation protocols (1,2), embryo handling and culture conditions (3), technical factors, such as the use of the transfer catheter and placement of the embryo during ET, (49) and embryo selection techniques (10,11). However, identification of clinical markers of endometrial receptivity for optimization during COH remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these proposed factors include characteristics of the catheter [1], operator experience [2], the site of uterine cavity where the embryo is transferred [3-6], presence of mucus or blood on the catheter following withdrawal [7], uterine contractions secondary to uterine manipulations, and difficulty passing through the cervix [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Cenksoy et al [17] reported that the optimal position of the air bubble seems to be a distance of <10 mm from the endometrial fundus, in accordance with Friedman et al [34]. Rovei et al [22] concluded that the embryo(s) must be replaced between 5 and 15 mm from the endometrial fundus. This is in line with previous results from our study group - the position of the transfer air bubbles after embryo transfer closer to the endometrial fundus resulted in higher pregnancy rates [24].…”
Section: Discussionmentioning
confidence: 53%
“…Despite its relevance, the technique used in embryo transfer has received little attention and progress until recent years [2,3]. Several studies [13,17,18,19,20,21,22,23] have demonstrated that the depth of the embryo placement into the uterine cavity, as a result of the embryo transfer technique, should be considered an important factor concerning pregnancy rates. Our research group pointed out that despite standardization of the transfer by protocol, the final position of the transferred air bubbles including the embryo(s) was not accurately predictable because of dependency of the injection speed which depends on the force used to press the plunger, the resistance of the plunger and a possible uterine resistance during transfer [24].…”
Section: Introductionmentioning
confidence: 99%